Обращение с обедненным ураном - Токаревский, В.В. (Ядерна та радіаційна безпека, 2015)
Рассмотрены эффекты радиологического и токсического воздействия обедненного урана на организм людей, образование радиоактивных аэрозолей, учет урана-236 в составе обедненного урана, влияние мощных источников бета-излучений при распаде урана-238. Проанализированы риски использования оружия с обедненным ураном. Розглянуто ефекти радіологічного й токсичного впливу на організм людей збідненого урану, утворення радіоактивних аерозолів , наявність урану-236 у складі збідненого урану, вплив потужних джерел бета-випромінювань при розпаді урану-238. Проаналізовано ризики використання зброї із збідненим ураном. The paper considers radiological and toxic impact of the depleted uranium on the human health. Radiological influence of depleted uranium is less for 60 % than natural uranium due to the decreasing of short-lived isotopes uranium-234 and uranium-235 after enrichment. The formation of radioactive aerosols and their impact on the human are mentioned. Use of the depleted uranium weapons has also a chemical effect on intake due to possible carcinogenic influence on kidney. Uranium-236 in the substance of the depleted uranium is determined. The fact of beta-radiation formation in the uranium-238 decay is regarded. This effect practically is the same for both depleted and natural uranium. Importance of toxicity of depleted uranium, as the heavier chemical substance, has a considerable contribution to the population health. The paper analyzes risks regarding the use of the depleted uranium weapons. There is international opposition against using weapons with depleted uranium. Resolution on effects of the use of armaments and ammunitions containing depleted uranium was five times supported by the United Nations (USA, United Kingdom, France and Israel did not support). The decision for banning of depleted uranium weapons was supported by the European Parliament.